Pengaruh Pendidikan Kewirausahaan dan Lingkungan Keluarga terhadap Minat Berwiraushaa Siswa Kelas XI SMKN 1 Singaraja - hasanah, Arlan; Dharmayasa, I Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to determine the process of testing the influence of Entrepreneurship Education and family environment on entrepreneurial interest partially and simultaneously. In this study, the population used was 231 students of class XI SMKN 1 Singaraja. This study uses quantitative data with a data collection method through a questionnaire. Data processing uses the assistance of the Statistical Package for The Social Science (SPSS) version 25 program. The data analysis technique used is multiple linear regression analysis with partial (t-test) and simultaneous (F-test) hypothesis testing. The results of this study indicate that (1) partially Entrepreneurship Education has a positive and significant effect on entrepreneurial interest, (2) partially the family environment has a positive and significant effect on entrepreneurial interest, and (3) simultaneously Entrepreneurship Education and family environment on entrepreneurial interest.